2022
DOI: 10.3389/fpls.2022.884443
|View full text |Cite
|
Sign up to set email alerts
|

TCP Transcription Factors Involved in Shoot Development of Ma Bamboo (Dendrocalamus latiflorus Munro)

Abstract: Ma bamboo (Dendrocalamus latiflorus Munro) is the most widely cultivated clumping bamboo in Southern China and is valuable for both consumption and wood production. The development of bamboo shoots involving the occurrence of lateral buds is unique, and it affects both shoot yield and the resulting timber. Plant-specific TCP transcription factors are involved in plant growth and development, particularly in lateral bud outgrowth and morphogenesis. However, the comprehensive information of the TCP genes in Ma b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 83 publications
(99 reference statements)
3
5
0
Order By: Relevance
“…These results suggest that segmental duplication is the predominant duplication event for DnTCP genes and is the primary driver of the expansion of the TCP gene family of D. nobile . This conclusion is consistent with previous studies on Populus euphratica ( Ma et al., 2016 ), Citrus sinensis ( Liu D. H. et al., 2022 ), and Ma Bamboo ( Jin et al., 2022 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that segmental duplication is the predominant duplication event for DnTCP genes and is the primary driver of the expansion of the TCP gene family of D. nobile . This conclusion is consistent with previous studies on Populus euphratica ( Ma et al., 2016 ), Citrus sinensis ( Liu D. H. et al., 2022 ), and Ma Bamboo ( Jin et al., 2022 ).…”
Section: Resultssupporting
confidence: 93%
“…Since transcription factors regulate the transcription of target genes within the nucleus, DnTCPs are likely to be localized in the nucleus. Some studies have analyzed the subcellular localization of Class I TCPs ( Jin et al., 2022 ; Yang et al., 2022 ; Ren et al., 2023 ). In this study, Class I TCPs, especially DnTCP9 and DnTCP18, were selected to investigate their subcellular localization, which could have unique roles in perianth development via binding to specific MADS-box.…”
Section: Resultsmentioning
confidence: 99%
“…There are 159 binding sites of TFs in DlCDP43 promoter, while the DlCDP4 promoter only contains 2 TFBS, which are GATA and HD-ZIP respectively. In previous studies, C2H2 TFs were shown to play an important role in bamboo shoot development ( Guo et al., 2022 ), and TCP TFs were implicated in rhizome bud growth and shoot development ( Jin et al., 2022 ). This led us to examine TFBS of these families in DlCDP promoters.…”
Section: Resultsmentioning
confidence: 99%
“…Duplication event researches have shown that segmental duplications are the main driving force for expansion and evolution of the TCP gene family (Cannon et al, 2004;Wang et al, 2012). In support to these findings, research in Tartary buckwheat (Yang M. et al, 2022), and M. acuminata (Wang J. et al, 2022) have shown that the segmental duplication was responsible for the expansion of TCP gene family, and that the TCP gene family has undergone three WGDs during evolution. Therefore, to further understand the gene duplication events of TCP members in 17 different plant species, we computed for duplication event types using the plant duplicate gene database, PDGD (http://pdgd.njau.edu.cn8080) (Lee et al, 2012) (Figure 5).…”
Section: Tcp Gene Family Duplication Eventsmentioning
confidence: 89%
“…Nonetheless, distinctions have not been made whether the class I or class II TCP subfamily was the first to appear in plant kingdom due to the fact that lower plants believed to be first forms of plant life like Marchantia polymorpha carry both classes (Sharma et al, 2013). Some predictions have displayed the CIN-like TCP sub-clade in the Class II, to be more ancestral than the CYC/TB1-like TCPs since the Class II TCPs belong to the CIN-like TCP sub-clade in the non-vascular plants (Wang J. et al, 2022). Further classifications of the TCP sequences have been shown within the phylogenetic analyses into smaller groups of high sequence similarity and possibly biological functionality.…”
Section: Phylogenetics and Evolution In Tcp Gene Familymentioning
confidence: 99%